A new instrument to measure high value, cost-conscious care attitudes among healthcare stakeholders: development of the MHAQ - Serge B. R. Mordang; Karen D. Könings; Andrea N. Leep Hunderfund; Aggie T. G. Paulus; Frank W. J. M. Smeenk; Laurents P. S. Stassen (BMC, 2020)
Abstract Background Residents have to learn to provide high value, cost-conscious care (HVCCC) to counter the trend of excessive healthcare costs. Their learning is impacted by individuals from different stakeholder groups within the workplace environment. These individuals' attitudes toward HVCCC may influence how and what residents learn. This study was carried out to develop an instrument to reliably measure HVCCC attitudes among residents, staff physicians, administrators, and patients. The instrument can be used to assess the residency-training environment. Method The Maastricht HVCCC Attitude Questionnaire (MHAQ) was developed in four phases. First, we conducted exploratory factor analyses using original data from a previously published survey. Next, we added nine items to strengthen subscales and tested the new questionnaire among the four stakeholder groups. We used exploratory factor analysis and Cronbach's alphas to define subscales, after which the final version of the MHAQ was constructed. Finally, we used generalizability theory to determine the number of respondents (residents or staff physicians) needed to reliably measure a specialty attitude score. Results Initial factor analysis identified three subscales. Thereafter, 301 residents, 297 staff physicians, 53 administrators and 792 patients completed the new questionnaire between June 2017 and July 2018. The best fitting subscale composition was a three-factor model. Subscales were defined as high-value care, cost incorporation, and perceived drawbacks. Cronbach's alphas were between 0.61 and 0.82 for all stakeholders on all subscales. Sufficient reliability for assessing national specialty attitude (G-coefficient > 0.6) could be achieved from 14 respondents. Conclusions The MHAQ reliably measures individual attitudes toward HVCCC in different stakeholders in health care contexts. It addresses key dimensions of HVCCC, providing content validity evidence. The MHAQ can be used to identify frontrunners of HVCCC, pinpoint aspects of residency training that need improvement, and benchmark and compare across specialties, hospitals and regions.